2017
DOI: 10.1016/j.memsci.2017.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Influence of PVP content on degradation of PES/PVP membranes: Insights from characterization of membranes with controlled composition

Abstract: Sodium hypochlorite is widely used to clean/sanitize PES/PVP membranes. However, this strong oxidant is responsible for accelerated polymer ageing, thus impairing PES/PVP membrane lifespan. This work aimed at getting a better understanding of the role of PVP in the degradation of PES/PVP membranes. As the precise chemical composition of commercial membranes is most often unknown, PES/PVP membranes with various PVP to PES ratios (from 0 to 44 wt %) were synthesized and aged dynamically by filtering sodium hypoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 26 publications
6
41
0
Order By: Relevance
“…Table 2 exhibits a noticeable change of the commercial PES membrane pure water permeance and BSA rejection before and after exposure to hypochlorite solution at pH 7.4. The observed finding is in agreement with the reported performance of PES membranes on chlorine exposure 91 . PES membranes were selected to emphasize the role of the sulfonated backbone for membrane chlorine stability.…”
Section: Resultssupporting
confidence: 88%
“…Table 2 exhibits a noticeable change of the commercial PES membrane pure water permeance and BSA rejection before and after exposure to hypochlorite solution at pH 7.4. The observed finding is in agreement with the reported performance of PES membranes on chlorine exposure 91 . PES membranes were selected to emphasize the role of the sulfonated backbone for membrane chlorine stability.…”
Section: Resultssupporting
confidence: 88%
“…The hypothesized chemical structure of the top-layer (Figure 1) would however not result in such a zeta potential curve, as the functional groups able to provide charge are terminal OH-groups, which are not deprotonated in this pH-range. Qualitatively similar results with respect to negative electrokinetic charge density for other polymers bearing no ionizable groups have been reported [32] and are expected to originate from specific adsorption of hydroxide ions from the feed on the membrane surface [33]. Additionally, there are no big changes in the zeta potential curves of the bare XL-PI support and the TFC membrane.…”
Section: Zeta Potential 3123supporting
confidence: 81%
“…However, permeability of membranes aged by NaClO at pH 9 and 11 were increased to 5.75 and 3.84 times of that of the pristine membrane, respectively. Although the extent of increase varied depending on exposure dose and aging conditions, permeability increase of PES membrane due to NaClO aging has been reported in many studies [13,16,17,32,33,34], and it was commonly attributed to the increase of pore size and porosity [11]. The similar permeability of pristine, control, and H 2 O 2 -aged membranes suggested that pore structure of the PES membrane was not altered obviously by alkaline or H 2 O 2 under the aging conditions in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the incorporation of chloride was observed for NaClO aging, and the atomic percentage of chloride for membrane aged at pH 9 was almost twice of that at 11. Chloride was introduced onto the surface of NaClO-aged membranes in the form of a phenyl chloride group along with the formation of sulfonic acid group during PES chain scission [13,14,40]. The higher percentage of chloride for the membrane aged by NaClO at pH 9 indicated more serious PES chain scission by NaClO aging at pH 9.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation